Inducing rostrum interfacial waves by fluid-solid coupling in a Chinese river dolphin (Lipotes vexillifer) - Song, Zhongchang; Zhang, Yu; Wei, Chong; Wang, Xianyan (AMER PHYSICAL SOC, 2016)
Through numerically solving the appropriate wave equations, propagation of biosonar signals in a Chinese river dolphin (baiji) was studied. The interfacial waves along the rostrum-tissue interfaces, including both compressional (longitudinal) and shear (transverse) waves in the solid rostrum through fluid-solid coupling were examined. The baiji's rostrum was found to effect acoustic beam formation not only as an interfacial wave generator but also as a sound reflector. The wave propagation patterns in the solid rostrum were found to significantly change the wave movement through the bone. Vibrations in the rostrum, expressed in solid displacement, initially increased but eventually decreased from posterior to anterior sides, indicating a complex physical process. Furthermore, the comparisons among seven cases, including the combination of (1) the rostrum, melon, and air sacs; (2) rostrum-air sacs; (3) rostrum-melon; (4) only rostrum; (5) air sacs-melon; (6) only air sacs; and (7) only melon revealed that the cases including the rostrum were better able to approach the complete system by inducing rostrum-tissue interfacial waves and reducing the differences in main beam angle and -3 dB beam width. The interfacial waves in the rostrum were considered complementary with reflection to determine the obbligato role of the rostrum in the baiji's biosonar emission. The far-field beams formed from complete fluid-solid models and non-fluid-solid models were compared to reveal the effects brought by the consideration of shear waves of the solid structures of the baiji. The results may provide useful information for further understanding the role of the rostrum in this odontocete species.